The Design and Manufacturing of HL-2M Vacuum Vessel. (17th November 2021) - Ran, Hong; Song, Binbin; Hou, Jilai; Zhang, Dangshen; Huang, Yuncong; Tang, Le; Yang, Qinwei; Cao, Zen; Wu, Xiaoqiang
Abstract: The HL-2M tokamak is an upgraded device of the HL-2A tokamak. As one of the main components of the HL-2M, the vacuum vessel (VV) is required to have a reliable structure and be manufactured with well-established methods. The HL-2M VV is designed with a D-shaped cross section, double-thin-wall structure that consists of the inner shell, outer shell, ribs, and ports. The whole torus is welded with 20 sectors. Inconel 625 has been selected as the main material of the VV because of its good mechanical properties and high resistivity. The structural analysis is performed using ANSYS. The results show that the VV can meet the design requirements. The manufacturing process of the VV is described in detail. The VV was completed in March 2019, and the HL-2M device achieved its first plasma discharge in December 2020.